Surgical Decompression for Lumbar Spinal Stenosis; Systematic Review and Meta-analysis - Rahman, Md Moshiur; Khan, Robert Ahmed; Nabi Khan, SIM Khairun; Uddin, Md Zia (Bangladesh Journal of Neurosurgery, 2022)
The primary concern for symptomatic back pain in elderly patients is to treat them according to guidelines. Surgical decompression for lumbar spinal stenosis may be laminotomy, laminectomy, or unilateral approach. Endoscopic or microscopic approaches are also promising though bony decompression is still the gold standard. Functional evaluation for instability, endplate changes, facet hypertrophy, and diagnostic tools like electrophysiological studies have been proposed. ODI, Swiss Score, and other back pain questionnaires assess the need for surgery. Here in this article, the authors have done a literature review with PRISMA analysis for surgical decompression in lumbar spinal stenosis with a ten-year database from Google Scholar, PubMed and Medline. Bang. J Neurosurgery 2021; 11(1): 36-40